RELATIONSHIPS BETWEEN ASSERTIVENESS AND PSYCHOLOGICAL AND SOCIAL PSYCHOLOGICAL CHARACTERISTICS OF PERSONALITY - Sheinov, V.P. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2018)
Assertiveness of an individual is studied as an ability to protect their own rights with confidence and dignity, without violating the rights of others. The purpose of the empirical research is to establish the links between the personal assertiveness and psychological and socio-psychological characteristics, and to create a social psychological “portrait” of an assertive individual. 1271 people have been tested including 644 men aged 17-75 (M = 40) and 627 women aged 17-78 (M = 42), all of various professions, backgrounds, social positions and regions. It has been identified that assertiveness is interconnected with the psychological gender. The following factors attribute to the assertiveness in both males and females: a) high indicators of their masculinity; b) gender harmony (high common number of masculine and feminine characteristics); c) androgyny of the individual. In women, assertiveness correlates negatively with femininity; in men, these two characteristics are not linked together. It is shown that assertiveness is positively related to extraversion, communicative skills, self-efficiency, self-respect, constructive aggression; it is negatively related to neuroticism, anxiety, depression and dependent behaviour. The results in some cases are different from those received during foreign studies: in particular, it has been established that the biological gender impacts the links between assertiveness levels and other psychological characteristics of an individual. The characteristics revealed during this research, together with the ones from previous researches, allowed the author to create a “socio psychological portrait” of an assertive person.